Critical Factors in the Preparation Stage to Achieve the Sustainability of Irrigation PPP Projects in Indonesia: a Qualitative Study - Saufika Hanjani; Erwin Saraswati; Noval Adib (Eduvest - Journal of Universal Studies, 2025)
This study aims to identify key success factors (Critical Success Factors (CSF) at the stage of preparing the Government-Business Cooperation (PPP) project in the water resources sector in Indonesia, by integrating a sustainability perspective. The problems raised are the low effectiveness of PPP project preparation which results in delays in implementation, as well as the lack of studies that adopt a sustainability approach and involve a multi-stakeholder perspective. This research uses a qualitative approach through a case study on the Komering Irrigation Area PPP Project. Data were collected through semi-structured interviews with seven informants from the public, private, and public sectors, then analyzed using thematic analysis techniques. The results of the study identified 19 CSF indicators grouped into six main categories: economic and financial viability, balance of risk allocation, policy and regulation, institutional and managerial capacity, stakeholder engagement and support, and technical scope. The majority of CSFs found are closely related to the economic and social dimensions of sustainability. These findings demonstrate the importance of a tripartite approach and the Triple Bottom Line principle in designing PPP project preparation strategies that are adaptive to sustainability challenges. This research makes a theoretical and practical contribution to the development of sustainable PPP, although it is limited to the actors directly involved in the project. Follow-up studies are suggested to expand the scope of actors and contexts to make the results more comprehensive and applicative.